Evaluation of the National Youthreach Programme - Emer Smyth; Joanne Banks; Jessica O'Sullivan; Selina MacCoy; Paul Redmond; Seamus McGuinness (The Economic and Social Research Institute (ESRI), 2019)
ESRI research, funded by Solas, examines the effectiveness of the programme aimed at young people who leave school early. It finds that the Youthreach programme helps young people who leave school early to have a positive experience of teaching and learning, supports the development of their personal and social skills, and offers many of them the qualifications to access further education, training and employment. However, the study also identifies a number of ways the programme could reach more young people and address their needs more effectively.
Keywords: 330